2021
DOI: 10.33314/jnhrc.v19i1.3245
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Radiological Outcome and Health Related Quality of Life after Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: Background: Posterior spinal surgery for adolescent idiopathic scoliosis is aimed at correcting deformity and stopping deformity progression to improve the health related quality of life. The correlation between radiological outcome and health related quality of life is yet unclear. This study aimed to assess the correlation between radiological outcome and health related quality of life.Methods: A descriptive cross-sectional study of 31 cases of adolescent idiopathic scoliosis who underwent posterior spinal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…6 Likewise, Chaudhary et al, reported similar findings (p-values of SRS-30 function and pain correlation analyses with curve correction: 0.688 and 0.453, respectively). 37 Moreover, our results showed that total fused levels were not associated with function or pain. Likewise, existing literature has reported that despite resulting in better ROM, fewer fusion levels did not correlate with SRS-22 function and pain in 2-10 years of follow-up.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…6 Likewise, Chaudhary et al, reported similar findings (p-values of SRS-30 function and pain correlation analyses with curve correction: 0.688 and 0.453, respectively). 37 Moreover, our results showed that total fused levels were not associated with function or pain. Likewise, existing literature has reported that despite resulting in better ROM, fewer fusion levels did not correlate with SRS-22 function and pain in 2-10 years of follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, our findings are in agreement with previous studies that have reported the irrelevance of Cobb angle correction degree with postoperative SRS-30 function and pain. 6,37 A study by Ghandehari et al, revealed that the percentage of radiographic correction was positively correlated only with the total SRS-30 score (r=0.52, p<0.001) and the satisfaction domain (r=0.386, p=0.026) but not with the function and pain domains. 6 Likewise, Chaudhary et al, reported similar findings (p-values of SRS-30 function and pain correlation analyses with curve correction: 0.688 and 0.453, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…7 Likewise, Chaudhary et al, reported similar findings (p-values of SRS-30 function and pain correlation analyses with curve correction: 0.688 and 0.453, respectively). 39 Moreover, our results showed that total fused levels were not associated with function or pain. Likewise, existing literature has reported that despite resulting in better ROM, fewer fusion levels did not correlate with SRS-22 function and pain in 2-10 years of follow-up.…”
Section: Prayer Quality Assessment As An Adjuvant Of Qol Measurement ...mentioning
confidence: 55%
“…Moreover, our findings are in agreement with previous studies that have reported the irrelevance of Cobb angle correction degree with postoperative SRS-30 function and pain. 7,39 A study by Ghandehari et al, revealed that the percentage of radiographic correction was positively correlated only with the total SRS-30 score (r=0.52, p<0.001) and the satisfaction domain (r=0.386, p=0.026) but not with the function and pain domains. 7 Likewise, Chaudhary et al, reported similar findings (p-values of SRS-30 function and pain correlation analyses with curve correction: 0.688 and 0.453, respectively).…”
Section: Prayer Quality Assessment As An Adjuvant Of Qol Measurement ...mentioning
confidence: 98%
“…Previous studies reported that the mean major Cobb angle correction rate after AIS corrective surgery ranged from 58.7% to 71.4% [12][13][14]. Meanwhile, surgical treatment can not only provide an improvement in radiological outcomes, but is also significantly positively correlated with pain, quality of life, self-image, and satisfaction after surgery [15,16]. Severe scoliosis might even impact cardiac and lung function.…”
Section: Introductionmentioning
confidence: 99%